Analysis of student WEB survey - Murauskas, Gediminas; Radavičius, Marijus (Lietuvos matematikos rinkinys, 2011)
In the paper the problem of adjustment for nonresponse in a WEB survey is addressed. The study is based on Vilnius University student survey on quality assessment of information technology services. A conditional logistic regression model is applied along with traditional nonresponse adjustment methods.